PERBEDAAN INDEKS PRESTASI KUMULATIF (IPK) MAHASISWA ANTARA GAYA BELAJAR VISUAL, AUDITORIAL DAN KINESTETIK PADA PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG - Zahruddin Hodsay (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
This research titled Differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang. The problem in this research was “whether or not differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang?”. The objective of this research was to find out whether or not Differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang. The method used comparative test over two averages and the approach used a quantitative approach. The data were collected by the documentation and questionnaires. The population of this research was 129 students were taken from the eighth level students PGRI University of Palembang academic year 2014/2015 and the sample of this research was 98 students. The data analysis used the comparative test over two averages.The result of this research was obtained a visual learning style 3.29, auditory learning style 3.23, and kinesthetic learning style 3.23. Hypothesis test used comparative over two averages Fcount 1.36 with standard error Ftable α 0.05 find out 3.10. so 1.36 < 3.10 then Ha was rejected and Ho was accepted so no differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang.